A four-year, systems-wide intervention promoting interprofessional collaboration - Braithwaite Jeffrey; Westbrook Mary; Nugus Peter; Greenfield David; Travaglia Joanne; Runciman William; Foxwell A Ruth; Boyce Rosalie A; Devinney Timothy; Westbrook Johanna (BMC, 2012)
Abstract Background A four-year action research study was conducted across the Australian Capital Territory health system to strengthen interprofessional collaboration (IPC) though multiple intervention activities. Methods We developed 272 substantial IPC intervention activities involving 2,407 face-to-face encounters with health system personnel. Staff attitudes toward IPC were surveyed yearly using Heinemann et al's Attitudes toward Health Care Teams and Parsell and Bligh's Readiness for Interprofessional Learning scales (RIPLS). At study's end staff assessed whether project goals were achieved. Results Of the improvement projects, 76 exhibited progress, and 57 made considerable gains in IPC. Educational workshops and feedback sessions were well received and stimulated interprofessional activities. Over time staff scores on Heinemann's Quality of Interprofessional Care subscale did not change significantly and scores on the Doctor Centrality subscale increased, contrary to predictions. Scores on the RIPLS subscales of Teamwork & Collaboration and Professional Identity did not alter. On average for the assessment items 33% of staff agreed that goals had been achieved, 10% disagreed, and 57% checked neutral. There was most agreement that the study had resulted in increased sharing of knowledge between professions and improved quality of patient care, and least agreement that between-professional rivalries had lessened and communication and trust between professions improved. Conclusions Our longitudinal interventional study of IPC involving multiple activities supporting increased IPC achieved many project-specific goals. However, improvements in attitudes over time were not demonstrated and neutral assessments predominated, highlighting the difficulties faced by studies targeting change at the systems level and over extended periods.